(untitled) - Hopkins, Bruce R. (Hoboken, N.J., 2003)
An essential resource on the new law facing nonprofits. An inability to adequately penalize nonprofits and individuals who collect excessive compensation or other benefits from tax-exempt organizations has led to the creation of intermediate sanctions–fines and legal actions intended to eliminate nonprofit abuse. Nonprofit legal expert Bruce R. Hopkins explains the constitution and application of these new rules in The Law of Intermediate Sanctions: A Guide for Nonprofits. This comprehensive, easy-to-use guide summarizes, analyzes, and explains the federal tax law on intermediate sanctions. Among other topics, the author addresses: The statute, legislative history, regulations, and court opinions of intermediate sanctions, The influence of law concerning private inurement, private benefit, and private foundation self-dealing
Keywords: Nonprofit organizations,Employee fringe benefits,Executives,Tax penalties; Taxation,Law and legislation,Taxation,Law and legislation,Taxation,Law and legislation; United States,United States,United States,United States